DESIGNING SUSTAINABLE AND HEALTHY HOMES - Mundo-Hernández, Julia J.; Hernández-Alvarez, Julia; Valerdi-Nochebuena, Cristina; Sosa-Oliver, Jorge (European Scientific Journal, ESJ, 2014)
Recent research in the field of architecture and building systems is focused on providing solutions that decrease energy consumption whilst producing less CO2 emissions and providing users´ comfort. These solutions include: utilising less building materials that come from sustainable and local sources, specifying more efficient lighting and home appliances, maximising the use of natural ventilation and daylight, integrating renewable energy technology and efficient heating, ventilation and air conditioning systems. However, few researchers and designers have concentrated their efforts on providing healthy and affordable built environments. The main aim of this research is to design a sustainable home with passive and active systems that could improve the health of the inhabitants of a poor Mexican town called Azumiatla (latitude: 19o N, altitude: 2,100 m, temperate climate). This community lacks of regular access to drinking water, sewage connection, toilets and rubbish collection service. A previous study have shown that houses have no daylight access or views, have minimum natural ventilation, and are built with poor thermal and acoustic materials such as cardboard sheets, steel sheets and concrete block (Mundo et al, 2010). Architectural proposals developed for Azumiatla include: local materials, walls and roof materials with good thermal and acoustics properties, “dry” toilets, green roof, vegetable garden, daylight access, natural ventilation, and energy efficient oven and lamps. Solar energy systems are considered. These proposals have taken into consideration the lifestyle and characteristics of the families in Azumiatla; and the methodology used has included the views and needs of the population.